Pengaruh Neuromuscular Electrical Stimulation Dan Latihan Pliometrik Terhadap Peningkatan Tinggi Lompatan Pada Pemain Bulutangkis - INDAH FITRIANA, NUR, Totok Budi Santoso , S.Fis , MPH, Dwi Rosella K, S,Fis., M.Fis (2015)
Background : Badminton players must have the technique to jump to the top of the well so that the player can do jumping smash perfectly. Eksplosive power leg muscles play an important role in the ability to jump to hit a smash, drop, and lob more quickly and accurately. To obtain powerful leg power can be supplied plyometrics training and additions NMES. Objective : To know the effect of Neuromuscular Electrical Stimulation and plyometrics training to increase height of the jump in badminton players. Methods : This research method using Quasi Experimental research design with pre and post test with control group design. To compare pre and post test results using the Wilcoxon Test, whereas the vertical jump to compare values between the experimental and control groups using Mann Whitney Test. Results : Wilcoxon test results pre and post test in the experimental group was of significant (p) < 0.05 means that there is the effect of NMES and plyomterics training to increase height of the jump. In the control group obtained sig (p) < 0.05 which means there is the effect of plyometric training to increase height of the jump. Mann Whitney Test obtained sig (p) < 0.05 which means that there is a difference between the effects of the experimental group and control group. Conclusion : Combine NMES and plyometrics training more influential compared to only plyometric training only.